1993
DOI: 10.1103/physrevb.47.16635
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-flux-induced conductance steps in microwires

Abstract: We predict a new type of steplike fluctuations in the magnetoconductance of three-dimensional ballistic microwires. These mesoscopic fluctuations, which appear on a scale corresponding to a small fraction of the quantum unit of magnetic flux 40=he/e, are a novel manifestation of the Aharonov-Bohm effect. The sharp conductance steps are caused by the shift of electronic levels through the Fermi level in a magnetic field. The flux-induced steps should be observable in, e.g. , submicrometer Bi whiskers at tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…The visual difference between UCF and geometrical fluctuations is only in their amplitudes. The geometrical fluctuations are enlarged parametrically in thick cylindrical wires, what has been observed in [13] in numerical simulations. On the other hand, these fluctuations can be viewed (even inside the correlation field H c ) as a series of randomly distributed e 2 /h conductance steps with the characteristic…”
Section: G]supporting
confidence: 65%
“…The visual difference between UCF and geometrical fluctuations is only in their amplitudes. The geometrical fluctuations are enlarged parametrically in thick cylindrical wires, what has been observed in [13] in numerical simulations. On the other hand, these fluctuations can be viewed (even inside the correlation field H c ) as a series of randomly distributed e 2 /h conductance steps with the characteristic…”
Section: G]supporting
confidence: 65%
“…In cylindrical channels with hard potential walls a similar mechanism leads, in a weak magnetic field, to the appearance of a sharp steplike structure of the conductance. 19 The inset in Fig. 5 portrays the Aharonov-Bohm oscillations for different but relatively close values of the parameter ϭ(EϪV 0 )/ប z .…”
Section: Longitudinal Magnetic Fieldsmentioning
confidence: 99%
“…Additionally, it was suggested that these systems could be used for investigations of quantum effects in electronic transport through nanowires and single-atom point contacts. 15 Electronic conductance in such 3D constrictions has been theoretically analyzed [17][18][19] using various models ͑e.g., contacts with symmetric cross sections characterized by hard walls, i.e., an infinite confining potential, with adiabatically varying shape, and in the limit of weak magnetic fields͒.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, inelastic scattering is assumed to occur only in the reservoirs, and strong elastic scattering at the contacts between the carbon nanotube and the leads. After detailed derivations, 33 the net electric and thermal currents are, respectively, given by …”
Section: Ballistic Transport In a Uniform B Fieldmentioning
confidence: 99%